Concussion in the international ice hockey World Championships and Olympic Winter Games between 2006 and 2015 - Tuominen, M.; Hänninen, T.; Parkkari, J.; Stuart, M. J.; Luoto, T.; Kannus, P.; Aubry, M. (British Journal of Sports Medicine, 2017)
Background: Concussions in sports are a growing concern. This study describes the incidence, injury characteristics and time trends of concussions in international ice hockey.